2014
DOI: 10.1074/jbc.m114.572636
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Rifamycin Polyketide Backbone Leads to Improved Drug Activity against Rifampicin-resistant Mycobacterium tuberculosis

Abstract: Background:The emergence of drug-resistant tuberculosis has called for the discovery of new antitubercular drugs. Results: We successfully generated 24-desmethylrifampicin by modifying the rifamycin polyketide backbone. Conclusion: 24-Desmethylrifamycin showed better antibacterial activity than rifampicin against multidrug-resistant strains of Mycobacterium tuberculosis. Significance: The combined genetic-synthetic strategy used in the study has opened up new avenues for generating more rifamycin analogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 43 publications
(44 reference statements)
0
71
0
Order By: Relevance
“…The numbers of species in this genus that are validly published have increased from 10 in 2000 to 68 in 2015 (http://www.bacterio.net/amycola topsis.html). These organisms possess several biosynthetic gene clusters (BGCs) that can be of biological importance [16], however the analysis based on the genome has been restricted to BGCs of balhimycin (bal), chloroeremomycin (cep) vancomycin (vcm), rifamycin (rif) [3,4]. The genomic studies have revealed that Amycolatopsis have comparatively large genomes *5 Mb (A. halophila YIM93223-10) to 10.86 Mb (A. balhimycina FH 1894), circular chromosomes and contains over 20 secondary metabolic gene clusters.…”
Section: General Features Of the Genus Amycolatopsismentioning
confidence: 99%
See 1 more Smart Citation
“…The numbers of species in this genus that are validly published have increased from 10 in 2000 to 68 in 2015 (http://www.bacterio.net/amycola topsis.html). These organisms possess several biosynthetic gene clusters (BGCs) that can be of biological importance [16], however the analysis based on the genome has been restricted to BGCs of balhimycin (bal), chloroeremomycin (cep) vancomycin (vcm), rifamycin (rif) [3,4]. The genomic studies have revealed that Amycolatopsis have comparatively large genomes *5 Mb (A. halophila YIM93223-10) to 10.86 Mb (A. balhimycina FH 1894), circular chromosomes and contains over 20 secondary metabolic gene clusters.…”
Section: General Features Of the Genus Amycolatopsismentioning
confidence: 99%
“…Within actinobacteria, members of genus Streptomyces contribute to almost 70-80 % of secondary metabolites while a small percentage is contributed by Amycolatopsis, Actinoplanes, Micromonospora and Saccharopolyspora [1]. Among these genera, the genus Amycolatopsis is of special importance for its capacity to produce several commercially and medicinally important antibiotics as balhimycin, vancomycin and rifamycin [2][3][4], other secondary metabolites as immuno-suppressants, anti-cancer agents etc. [5] and other applications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Further testing of the analogue against MDR strains of M. tuberculosis was done in association with Institute of Genomics and Integrative Biology (CSIR-IGIB), Delhi. The analogue 24-desmethylrifampicin was found to be better than the already existing rifampicin used against MDR strains [19]. Thus it can be hypothesised that, this drug could find application in pharmaceutical sector.…”
Section: Modification Of Rifamycin Polyketide Backbone: Generating Rimentioning
confidence: 96%
“…3). The derivatives of 24-desmethylrifamycin B: 24-desmethylrifampicin and 24-desmethylrifamycin S, were tested against MDR strains of M. tuberculosis, where the activity was found to be 10 times better than the existing commercially available rifampicin [19].…”
Section: Stepping Stones For Generation Of 24-desmethylrifampicinmentioning
confidence: 99%
“…A programmable antibiotic technique selectively targets the bacteria which harbor the resistant strains while leaving other microbes alone, which wipe out the bad bugs at once. 3 They succeeded by instructing a bacterial enzyme "Cas9" to target the particular DNA sequence and cut it up. This approach leaves the microbial community intact and can keep the resistance in check and prevent certain type of secondary infections, eliminating the two hazard associated with treatment by classical antibiotics.…”
mentioning
confidence: 99%